2019
DOI: 10.1111/nhs.12636
|View full text |Cite
|
Sign up to set email alerts
|

Influences of gender‐related perceptions and experiences on nursing professionalism: A cross‐sectional study

Abstract: The purpose of this study was to examine the influence of gender-related perceptions and experiences on nursing professionalism among nursing students who grew up in a culture with strong gender norms. Data were collected through an online survey from a convenience sample of nursing students in South Korea. To examine gender-related perceptions, we assessed beliefs in gender stereotypes and the level of benevolent sexism. Direct and indirect experiences of gender violence were assessed by examining participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Additional explanations for the differences in perception may be gender related. Park et al (2019) found that stronger gender stereotypes were associated with lower scores on the professionalism of nursing.…”
Section: Discussionmentioning
confidence: 96%
“…Additional explanations for the differences in perception may be gender related. Park et al (2019) found that stronger gender stereotypes were associated with lower scores on the professionalism of nursing.…”
Section: Discussionmentioning
confidence: 96%
“…The variables gender (item 1), undergraduate qualification (item 4), marital status (item 5) and employment sector (item 7) had no significant/practical association with any of the five HPS constructs. However, in international studies, gender [ 11 , 16 ] and undergraduate qualifications, specifically higher educational degrees [ 10 , 15 ], had an association with professionalism. Certain authors found that nurses pursuing bachelor’s degrees and higher were more attentive to professional values than nurses with lower educational levels [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dataset from Turkey was taken from a large‐scale study on the relationship between nursing students' beliefs about violence against women and their attitudes toward sexism and gender roles (IRB# 2018.063.IRB3.042). The Korean dataset was taken from a study on nursing professionalism in Korean nursing students, and how that related to their traditional gender‐related thoughts and attitudes (Park et al, ; IRB# 171116‐2A).…”
Section: Methodsmentioning
confidence: 99%
“…Sexist ideologies, oftentimes unnoticed, are associated with poorer health, lower rates of employment and management, and less political participation among women (Cassese & Holman, ; Eek & Axmon, ). Importantly, nurses who are educated in this sociocultural atmosphere tend to be highly influenced by cultural factors, particularly in terms of their professionalism, nursing image, and nursing performance (Park, Kwon, Kim, & Kim, ). Indeed, Western scholars have examined the concept of sexism in different settings in a wide range of population groups, including teachers, college students, and members of the public of different ethnic backgrounds (Cahill & Adams, ; Eaton & Matamala, ; Forbes, Doroszewicz, Card, & Adams‐Curtis, ; Pearson, ).…”
Section: Introductionmentioning
confidence: 99%